Ionizing radiation induced degradation of poly (2-methoxy-5-(2 '-ethyl-hexyloxy)-1,4-phenylene vinylene) in solution - Bronze-Uhle, E. S. [UNESP]; Batagin-Neto, A. [UNESP]; Lavarda, Francisco Carlos [UNESP]; Graeff, Carlos Frederico de Oliveira [UNESP] (American Institute of Physics (AIP), 2011)
In this paper we investigate the causes of the chromatic alteration observed in chloroform solutions of poly (2-methoxy-5-(2'-ethyl-hexyloxy)-1,4-phenylene vinylene) (MEH-PPV) after gamma ray irradiation. Structural and chemical changes were analyzed by gel permeation chromatography, fourier transform infrared spectroscopy, and proton nuclear magnetic resonance techniques and complemented by electronic structure calculations. The results indicate chlorine incorporation in the polymer structure and main chain scission after irradiation. Based on our findings we propose that the main mechanism for the blue-shifts, observed in the UV-Vis absorption spectra of MEH-PPV after irradiation, is the result of a radical attack on the polymer main chain. Gamma rays generate radicals, (center dot)Cl and (center dot)CHCl(2) from chloroform radiolysis that attack preferentially the vinyl double bonds of the polymer backbone, breaking the electronic conjugation and eventually the chain. Our results indicate that oxygen does not play a major role in the effect. Electronic spectra simulations were performed based on these assumptions reproducing the UV-Vis experimental results. (C) 2011 American Institute of Physics. [doi:10.1063/1.3644946]